Tropical Occurrence and Agricultural Importance of Beauveria bassiana and Metarhizium anisopliae - McGuire, Amy V.; Northfield, Tobin D. (Frontiers in Sustainable Food Systems, 2020)
Entomopathogenic fungi are often relied on as important components of integrated pest management in tropical agriculture, either as biopesticides or as naturally occurring microbes conserved in the environment. Tropical abiotic conditions are often well-suited for microbial growth, and tropical habitats can be teeming with microbial biodiversity. However, competitive interactions with other fungi and the need to overcome defenses of hosts adapted to high fungal loads may inhibit the ability of insect pathogens to control tropical pests. Here, we review the current literature on Beauveria bassiana and Metarhizium anisopliae inhabiting tropical environments and their potential use as biological control agents. In some cases there is not a clear distinction between temperate and tropical agroecosystems, such as in the level of organic matter or soil texture in agricultural soils. Therefore, the effects of these soil characteristics in temperate agroecosystems are likely applicable to tropical systems as well. In contrast, factors such as microbial biodiversity and seasonal fluctuation in environmental conditions can differ dramatically between temperate and tropical systems. Therefore, we discuss literature that can be generalized to tropical systems. Where temperate and tropical systems are likely to differ we synthesize the literature specifically for tropical agroecosystems. We also provide hypotheses to stimulate future work on latitudinal gradients and the relative importance of biotic and abiotic factors in governing entomopathogen prevalence and community composition. These hypotheses provide a path forward to developing theory guiding the conservation and augmentation of entomopathogenic fungi to prevent pest outbreaks.